(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The stilt houses... The landscape, by the Chilote poet Mario García Álvarez, has as its background the historical conditions that determine the work of poetic writing in the Tenth Region of Los Lagos. Writing that would be tense in advance by the dialectic of tradition and modernity as its condition of possibility. Perhaps it becomes the starting point for an interpretive instance that constitutes a particular relationship of poetic language and its articulation with memory, which is associated with a fact that determines it, namely, the loss of the world, defined as the subtraction of all the keys through which a given subject of enunciation articulates a relationship with a horizon of historical, political and naturally aesthetic meaning.